Experimental Investigation of the Ratio Between the Tensile Strength and Yield Stress of Reinforcing Bar - Md. Munirul Islam; Md. Nafiuzzaman; Md. Mushfiqur Rahman Chayon; Tahia Rahman Sinthia; Shahriar Montasir (Disaster in Civil Engineering and Architecture, 2025)
Steel is an iron alloy with additional carbon to improve its strength and fracture resistance. Reinforcing steel, also known as rebar, is a steel bar that’s added to concrete to strengthen it. This study provides a comprehensive analysis of the tensile strength-to-yield stress (TS/YS) ratio and its implications for the ductility and performance of steel in structural applications, with a particular focus on earthquake-resistant design. Ductility is essential for preventing structural collapse during extreme events. The (TS/YS) ratio is crucial for structural systems expected to endure strain-hardening range stresses. The relevance of this ratio in the design of buildings and bridges is emphasized, especially regarding ductile elements and stress concentrations. Building codes, including the Bangladesh National Building Code (BNBC 2020) and the American Concrete Institute (ACI) 318M-14, mandate that the (TS/YS) ratio exceed 1.25, and guarantee adequate inelastic rotation capacity in structural members. This experimental investigation broadly evaluates Grades 40, 60, and 72.5 rebars with different diameters of 12 mm, 16 mm, and 20 mm, providing insights into the variation of TS/YS ratios across a broad strength spectrum to ensure structural reliability and optimize material selection. The results show that despite of higher yield stress of 72.5 grade bar (86 ksi), 60 grade bar shows better TS/YS ratio of 1.55. Elongation rates remained within acceptable limits for both 60 and 40 grade bar which is 21%, although the 72.5-grade rebar exhibited slightly lower elongation. Displacement-controlled tensile tests captured full stress-strain curves, indicating that the 60-grade rebar outperformed the others, particularly at the 16 mm diameter. Necking and complete cup-cone failure is found for 12 mm rebars. Overall, this experiment supports the feasibility of utilizing higher-grade rebars, especially Grade 60, in special structural systems to enhance ductility and performance during seismic events.